BLADE RUNNER IN THE TIME WARP COMPLEX: THE MOVIE BY RIDLEY SCOTT IN SHONO YORIKO’S NOVEL - Kubiak-Ho-Chi, Beata (Porównania, 2016)
Blade Runner, the title of Ridley Scott’s cult movie (1982), emerges on the pages of the novel Time Warp Complex (Taimu surippu konbināto, 1994) by Shōno Yoriko (b. 1956), a contemporary Japanese woman writer, as an envoy from the bleak future. What connects these two works belonging to different narrative forms, both visual and textual? What kind of inspiration does Shono draw from the Blade Runner and what are its implications for the novel’s plot? To what extent does the post-apocalyptic, science-fictional world of Ridley Scott’s movie permeate the slipstream literature of Shōno Yoriko, shaping its fictional reality? Apart from answering above questions, the author of the present article also considers the role of science-fiction in contemporary Japanese literature, along with presenting the profile and literary work of Shōno Yoriko, an outstanding woman writer – but so far, for various reasons, little known outside Japan.